Consumers' Preference of Fast Food Items in Kathmandu Valley - Rai, Bharat; Rawal, Rajshree R (NCC Journal, 2019)
The main purpose of this study is to understand and evaluate the factors affecting consumer's preference of fast food items in Kathmandu Valley. Taste, price, ambience and location have been taken as independent variables and brand preference has been taken as dependent variable in the study. The study has been adopted the descriptive and causal research design. Samplesize has been taken 226 under the study. Primary data for the research has-been collected using structured questionnaire from fast food consumer within Kathmandu Valley of University students. To analyze the collected data, descriptive statistics, and Pearson correlation as well as regression analysis has been conducted to identify the relationship and effect between independent variables (taste, price, ambience and location) and dependent variable (consumer preference). SPSS has been used to process the data and to find the result of the data analysis. By the correlation analysis there is significant relationships between independent variables (taste, price, ambience and location) and dependent variable (brand preference). Based on regression analysis, taste, ambience and location have significant and positive impact on consumer preference for fast food items. It means consumers are much more concerned and aware about these factors while consuming the fast food. Similarly, price has less or no effect on consumer preference for fast food items for the respondents taken under the study.